2009
DOI: 10.1073/pnas.0902377106
|View full text |Cite
|
Sign up to set email alerts
|

Mental retardation linked to mutations in the HSD17B10 gene interfering with neurosteroid and isoleucine metabolism

Abstract: Mutations in the HSD17B10 gene were identified in two previously described mentally retarded males. A point mutation c.776G>C was found from a survivor (SV), whereas a potent mutation, c.419C>T, was identified in another deceased case (SF) with undetectable hydroxysteroid (17␤) dehydrogenase 10 (HSD10) activity. Protein levels of mutant HSD10(R130C) in patient SF and HSD10(E249Q) in patient SV were about half that of HSD10 in normal controls. The E249Q mutation appears to affect HSD10 subunit interactions, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 46 publications
1
51
1
Order By: Relevance
“…38 While SDR5C1 is ubiquitously expressed in all tissues, it is predominantly found in liver, heart, and brain. In the brain, it is primarily expressed in neural rather than in glial cells, implying that the loss of the dehydrogenase activity could cause neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…38 While SDR5C1 is ubiquitously expressed in all tissues, it is predominantly found in liver, heart, and brain. In the brain, it is primarily expressed in neural rather than in glial cells, implying that the loss of the dehydrogenase activity could cause neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…AF037438). The role of 17β-HSD10, after many debates and criticisms, has been clarified in more recent studies (163-174): it plays essential roles in neurosteroidogenesis as well as in the isoleucine degradation pathway. This explains why a mutation(s) of this gene, HSD17B10 , may delay the brain development and/or result in the regression of brain functions even in the absence of Aβ peptide (167, 168, 174-176).…”
Section: Translocator Protein As a Therapeutic Target For Alzheimer'smentioning
confidence: 99%
“…As is well known, 17β-estradiol exhibits significant neuroprotective effects. Elevated levels of 17β-HSD10 found in Alzheimer's disease brains (164, 165, 168, 179) may take a part in the pathogenesis of Alzheimer's disease due to an imbalance of neuroactive steroid metabolism (164-170, 174, 177). …”
Section: Translocator Protein As a Therapeutic Target For Alzheimer'smentioning
confidence: 99%
“…1,4-11 However, three patients were identified who presented symptoms in the first days of life. 1, 11 It has recently been shown that symptoms of these patients are unrelated to accumulation of metabolites in the isoleucine pathway and that the neurological handicap can be associated with an imbalance in neurosteroid metabolism 12 or to defects in general mitochondrial function. 13 In addition, the splice variant c.574C4A of HSD17B10 gene has been associated with a new syndromic form of X-linked mental retardation, choreoathetosis and abnormal behaviour.…”
Section: Introductionmentioning
confidence: 99%